Reasons for admission in asylum-seeking and non-asylum-seeking patients in a paediatric tertiary care centre (Swiss Medical Weekly, 2020)
BACKGROUND In the last decade an increasing number of asylum-seeking children arrived in Europe and local healthcare systems have been challenged to adapt to their health needs. The aim of this study was to compare the spectrum of disease and management of asylum-seeking and non-asylum-seeking children requiring hospital admission. METHODS This was a retrospective cohort study including health data from recently arrived asylum-seeking and non-asylum-seeking children admitted between January 2016 and December 2017. Data were collected using electronic administrative and medical records. RESULTS Of 11,794 admissions of 9407 patients, 149 (1%) were asylum-seeking and 11,645 (99%) from non-asylum-seeking children. In asylum-seeking children the median age was 4 years (interquartile range [IQR] 0–13) with 61% males and in non-asylum-seeking children 4 years (IQR 0–11) years with 56% males. Respiratory infections accounted for 17–19% of admissions in both groups. Rare infectious diseases were more frequent in asylum-seeking children (15 vs 7%; difference in proportions 0.08, 95% confidence interval [CI] 0.02–0.14; p